Prevalence of metabolic syndrome among adults in sub-district hospital Akhnoor: a cross sectional study - Sharma, Chandan; Kumar, Sanjeev; Badyal, Ashima (International Journal of Advances in Medicine, 2020)
Background: Metabolic syndrome (MetS) is an aggregation of conditions that together increase the risk of cardiovascular disease in individuals, which would not otherwise be recognized. World-wide, its prevalence has been documented as 11-41%. It has become a major public health challenge globally due to rapid urbanization, sedentary lifestyle, and surplus energy intake. Methods: The present hospital-based-study was aimed at finding the prevalence of MetS in people attending OPD of medicine in sub-district hospital Akhnoor, Jammu: from November 2019 to April 2020. Study subjects included both males and females between the age group of 20-60 years attending the medicine OPD. Among the 400 participants, 185 were females and 215 were males. Patients were diagnosed as MetS according to national cholesterol education program adult treatment panel-III (ATP) criteria. Results: About 41.25% of the participants were below 40 years and 58.75% of the participants were above 40 years of age. A very high prevalence of 68.75% MetS was reported among patients, hinting at the changing lifestyle of the people. People of older age and with general obesity are under increased MetS risk. Prevalence among males (67.44%) and females (70.27%) differed only slightly. But our present study tends to suggest an increased risk among females, which is quite significant. Conclusions: Various researchers have associated MetS with depression and chronic diseases, which shows that the population is under graver risk with increased prevalence among masses. The prevalence in >40 years age group is showing rapid and alarming increase. Lifestyle modifications are crucial to the management of MetS.